2003
DOI: 10.1111/j.1460-9568.2003.02961.x
|View full text |Cite
|
Sign up to set email alerts
|

SR141716A reduces the reinforcing properties of heroin but not heroin‐induced increases in nucleus accumbens dopamine in rats

Abstract: The present experiments tested the hypothesis that the selective CB1 receptor antagonist SR141716A alters heroin self-administration by attenuating heroin-induced increases in nucleus accumbens dopamine levels. SR141716A pretreatment dose-dependently (0.3-3 mg/kg, i.p.) reduced operant heroin self-administration by male Wistar rats under a fixed ratio schedule of reinforcement, and significantly lowered the breaking point of responding for heroin under a progressive ratio schedule of reinforcement. These obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 26 publications
(42 reference statements)
9
75
1
1
Order By: Relevance
“…The correlation between the CB 1 receptor and heroin self-administration underscores the significant functional interactions between the cannabinoid and opioid systems. In line with previous studies, we also confirmed an acute pharmacological regulation of cannabinoid receptor modulation of opiate self-administration behavior (Caille and Parsons, 2003;Navarro et al, 2001;Solinas et al, 2003). Blockade of the CB 1 receptor with Rimonabant (at the 3 mg/ kg dose) inhibited heroin consumption, but there was no altered sensitivity in the THC-exposed rats, perhaps reflective of the lack of CB 1 receptor alterations.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between the CB 1 receptor and heroin self-administration underscores the significant functional interactions between the cannabinoid and opioid systems. In line with previous studies, we also confirmed an acute pharmacological regulation of cannabinoid receptor modulation of opiate self-administration behavior (Caille and Parsons, 2003;Navarro et al, 2001;Solinas et al, 2003). Blockade of the CB 1 receptor with Rimonabant (at the 3 mg/ kg dose) inhibited heroin consumption, but there was no altered sensitivity in the THC-exposed rats, perhaps reflective of the lack of CB 1 receptor alterations.…”
Section: Discussionsupporting
confidence: 92%
“…A number of previous studies have demonstrated that cannabinoid ligands can modulate the reinforcing effects (Caille and Parsons, 2003;DeVries et al, 2003;Navarro et al, 2001;Norwood et al, 2003;Solinas et al, 2003Solinas et al, , 2005 and locomotor effects (Cadoni et al, 2001;Lamarque et al, 2001;Pontieri et al, 2001;Rubino et al, 2003) of opioid agonists. In the case of psychomotor stimulants, there is some evidence that exposure to THC or cannabinoid agonists may lead to behavioral sensitization with amphetamine (Gorriti et al, 1999;Lamarque et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has recently been reported that one (Gorriti et al, 2005) or several (Moreno et al, 2005) injections of cannabinoid agonists render rats more sensitive to the effects of direct dopamine receptor agonists. Several studies have examined the ability of pharmacological or genetic blockade of cannabinoid receptors to alter the behavioral effects of cocaine (Caille and Parsons, 2003;Cossu et al, 2001;Martin et al, 2000;Soria et al, 2005;Tanda et al, 2000). For example, acute administration of the CB1 receptor agonist WIN55,202-5 can decrease cocaine self-administration (Fattore et al, 1999), and mice lacking the CB1 receptors show reduce reinforcing efficacy of cocaine (Soria et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genetic ablation of CB 1 receptors in mice greatly reduces both opiate self-administration (Ledent et al, 1999;Cossu et al, 2001) and opiateinduced conditioned place preference (Martin et al, 2000;Rice et al, 2002). Similarly, administration of the selective CB 1 receptor antagonist SR 141716A (Rimonabant) attenuates both morphine-induced conditioned place preference (Mas-Nieto et al, 2001) and heroin self-administration in rodents (Navarro et al, 2001;Caillé and Parsons, 2003;De Vries et al, 2003;Solinas et al, 2003). In addition, it has been shown that the reinforcing and motivational effects of heroin-paired stimuli are mediated, at least in part, by activation of cannabinoid CB 1 receptors (De Vries et al, 2003;Fattore et al, 2003).…”
Section: Introductionmentioning
confidence: 99%